Assessment of the Current State of Pharmacovigilance System in Pakistan Using Indicator-Based Assessment Tool - Khan, Muhammad Akhtar Abbas; Hamid, Saima; Ur-Rehman, Tofeeq; Babar, Zaheer-Ud-Din (Frontiers in Pharmacology, 2022)
Objectives: Pakistan felt the need for effective and robust pharmacovigilance (PV) system after one of the deadliest drug-related tragedies causing more than 300 deaths in 2012. The country set up its national PV center in 2015 and joined WHO’s Program for International Drug Monitoring (PIDM) in 2018 as a full member. The current study was aimed to evaluate the PV system's functionality, identify the gaps, areas of improvement, and a strategy to lead a functional PV system in Pakistan. Method: The descriptive cross-sectional study was conducted by providing an interviewer-administered questionnaire of the PV system across Pakistan by utilizing the Indicator based Pharmacovigilance assessment tool (IPAT). By convenience sampling method 36 study participants were selected from the Drug Regulatory Authority of Pakistan (DRAP), drug administration of provincial health departments of four provinces and federally affiliated areas, five national public health programs, and twenty three public & private hospitals. The assessment includes document review, interviews of the key informants by structured open-ended questions, and review of websites of relevant organizations. Results:DRAP with a national PV center received a 75 percent overall performance score on IPAT. To be regarded as "minimally functioning," a country's PV and drug safety system must meet all core indicators. DRAP scored 80.76 percent on the core indicators so cannot be deemed functional at this time. The only province with a regional PV center, Punjab, had scored 72.13 percent on relevant parameters. Despite receiving funding from the Global Fund, none of the National Public Health Programs (PHPs) have PV centers or associated activities. All hospitals except two private hospitals could not qualify the minimum requirements for functional PV. The absence of a legal framework for mandatory ADR reporting, lack of drug information center, budgetary constraints, no active surveillance activities, nonexistence of pharmacovigilance risk assessment expert committee, and insufficient coordination among stakeholders were identified as major gaps. Conclusion: The results of the study reveal that Pakistan’s PV system is not fully functional at all levels. A two-phased strategy encompassing the non-financial and financial interventions is proposed to improve the PV systems at the national, provincial, PHPs, and hospitals levels.